Changes in myocardial oxygenation and perfusion under pharmacological stress with dipyridamole: assessment using T*2 and T1 measurements - Wacker, Christian; Bock, Michael; Kaick, Gerhard van; Bauer, Wolfgang Rudolf; Schad, Lothar R. (Magnetic resonance in medicine, 1999)
The aim of this pilot-study was to evaluate changes in myocardial oxygenation and perfusion under pharmacological stress with dipyridamole (DIP) by means of MRI. Twenty healthy volunteers were examined using a multi-echo gradient-echo sequence. The differential myocardial signal response due to the blood oxygen level dependent (BOLD) effect was studied under variable conditions of myocardial oxygen supply caused by the vasodilator DIP. Unlike contrast agents (CA) methods, which require at least two injections of CA and DIP, the presented methods require only a single infusion of DIP. To assess changes in myocardial perfusion, a saturation recovery TurboFLASH (SRTFL) sequence with centric reordering for T1 measurements was used with global and slice-selective spin-preparation (five volunteers). The signal response was measured at baseline conditions and when myocardial blood flow was increased during pharmacological stress with DIP. Administration of DIP induced a 17 ± 9% increase in T*2. Enhanced perfusion resulted in a 15 ± 5% decrease of T1 after slice-selective spin preparation and a calculated increase in absolute perfusion of about 5.1 ml/(g × min), which reflects coronary reserve. The study shows that DIP-induced alterations in the relationship between myocardial oxygen supply and demand are detectable in healthy volunteers using T*2 and T1 measurements. A combination of T*2 and T1 examinations could become a useful diagnostic tool for the non-invasive assessment of myocardial oxygenation and perfusion in patients with coronary artery disease (CAD). Magn Reson Med 41:686-695, 1999. © 1999 Wiley-Liss, Inc.
Im Titel ist die "2" und die "1" bei T*2 und T1 tiefgestellt
Gesehen am 17.02.2021